2023
DOI: 10.1101/2023.12.18.566359
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

White matter hyperintensity genetic risk factorTRIM47regulates autophagy in brain endothelial cells

Sunny Hoi-Sang Yeung,
Ralph Hon-Sun Lee,
Gerald Wai-Yeung Cheng
et al.

Abstract: White matter hyperintensity (WMH) is strongly correlated with age-related dementia and hypertension, but its pathogenesis remains obscure. GWAS identified TRIM47 at 17q25 locus as a top genetic risk factor for WMH formation. TRIM family is a class of E3 ubiquitin ligase with pivotal functions in autophagy, which is critical for brain endothelial cell (ECs) remodeling during hypertension. We hypothesize that TRIM47 regulates autophagy and its loss-of-function disturbs cerebrovasculature. Based on transcriptomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Studies have reported that TRIM44 not only participates in the innate immunity against viral infection [31] but also acts as a bridge between cellular autophagy and the ubiquitin-proteasome degradation system [24]. Similarly, TRIM47 is involved in the innate immunity against viral infection [32] and is associated with neuronal autophagy [33], while TRIM56 regulates replication of many viruses [34,35]. Therefore, we chose to explore TRIM44, TRIM47, and TRIM56, as these TRIM proteins' mechanisms in RABV infection have not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that TRIM44 not only participates in the innate immunity against viral infection [31] but also acts as a bridge between cellular autophagy and the ubiquitin-proteasome degradation system [24]. Similarly, TRIM47 is involved in the innate immunity against viral infection [32] and is associated with neuronal autophagy [33], while TRIM56 regulates replication of many viruses [34,35]. Therefore, we chose to explore TRIM44, TRIM47, and TRIM56, as these TRIM proteins' mechanisms in RABV infection have not been studied.…”
Section: Discussionmentioning
confidence: 99%